(1.5-x)(2-x)-2=0

Simple and best practice solution for (1.5-x)(2-x)-2=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (1.5-x)(2-x)-2=0 equation:


Simplifying
(1.5 + -1x)(2 + -1x) + -2 = 0

Multiply (1.5 + -1x) * (2 + -1x)
(1.5(2 + -1x) + -1x * (2 + -1x)) + -2 = 0
((2 * 1.5 + -1x * 1.5) + -1x * (2 + -1x)) + -2 = 0
((3 + -1.5x) + -1x * (2 + -1x)) + -2 = 0
(3 + -1.5x + (2 * -1x + -1x * -1x)) + -2 = 0
(3 + -1.5x + (-2x + 1x2)) + -2 = 0

Combine like terms: -1.5x + -2x = -3.5x
(3 + -3.5x + 1x2) + -2 = 0

Reorder the terms:
3 + -2 + -3.5x + 1x2 = 0

Combine like terms: 3 + -2 = 1
1 + -3.5x + 1x2 = 0

Solving
1 + -3.5x + 1x2 = 0

Solving for variable 'x'.

Begin completing the square.

Move the constant term to the right:

Add '-1' to each side of the equation.
1 + -3.5x + -1 + x2 = 0 + -1

Reorder the terms:
1 + -1 + -3.5x + x2 = 0 + -1

Combine like terms: 1 + -1 = 0
0 + -3.5x + x2 = 0 + -1
-3.5x + x2 = 0 + -1

Combine like terms: 0 + -1 = -1
-3.5x + x2 = -1

The x term is -3.5x.  Take half its coefficient (-1.75).
Square it (3.0625) and add it to both sides.

Add '3.0625' to each side of the equation.
-3.5x + 3.0625 + x2 = -1 + 3.0625

Reorder the terms:
3.0625 + -3.5x + x2 = -1 + 3.0625

Combine like terms: -1 + 3.0625 = 2.0625
3.0625 + -3.5x + x2 = 2.0625

Factor a perfect square on the left side:
(x + -1.75)(x + -1.75) = 2.0625

Calculate the square root of the right side: 1.436140662

Break this problem into two subproblems by setting 
(x + -1.75) equal to 1.436140662 and -1.436140662.

Subproblem 1

x + -1.75 = 1.436140662 Simplifying x + -1.75 = 1.436140662 Reorder the terms: -1.75 + x = 1.436140662 Solving -1.75 + x = 1.436140662 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '1.75' to each side of the equation. -1.75 + 1.75 + x = 1.436140662 + 1.75 Combine like terms: -1.75 + 1.75 = 0.00 0.00 + x = 1.436140662 + 1.75 x = 1.436140662 + 1.75 Combine like terms: 1.436140662 + 1.75 = 3.186140662 x = 3.186140662 Simplifying x = 3.186140662

Subproblem 2

x + -1.75 = -1.436140662 Simplifying x + -1.75 = -1.436140662 Reorder the terms: -1.75 + x = -1.436140662 Solving -1.75 + x = -1.436140662 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '1.75' to each side of the equation. -1.75 + 1.75 + x = -1.436140662 + 1.75 Combine like terms: -1.75 + 1.75 = 0.00 0.00 + x = -1.436140662 + 1.75 x = -1.436140662 + 1.75 Combine like terms: -1.436140662 + 1.75 = 0.313859338 x = 0.313859338 Simplifying x = 0.313859338

Solution

The solution to the problem is based on the solutions from the subproblems. x = {3.186140662, 0.313859338}

See similar equations:

| 2x^4-4x^2-70=0 | | 46+-1+8x=12x+2 | | 3/10-1/5= | | 18=3x+1 | | 5a+3b-a-5b= | | x^4-3.5x^2+1=0 | | -3.8(2.7x-5.5)-8.4= | | z/.06=-7.98 | | y/8=3/11 | | (X+7)(X+14)=0 | | 7/4=5/b-4 | | -8a^2b-6ab+5b=0 | | 51-3x=3x | | ln(x)=ln(x-2)+ln(6) | | -4n-3(-8n+2)=134 | | 7-3y-4=5y | | 6x-(-2x)=-24 | | 51/6x=3x | | 2p^2-6p=0 | | 54n^2k+300nk-144k=0 | | (L)8LW=V | | -36p^2+136p+32=0 | | 6p+22= | | 5a^3b^3/15a^4b^2 | | 18x^6-2x^2=0 | | 1/7m=29 | | 2(2x+3)=50 | | 2(4f-8)=-21+5f | | 1/3x+7=-2 | | -5(x+5)=-5 | | (x^2)/(x^2-4)=0 | | 0=2x-24-338/x^2 |

Equations solver categories